Cave Tourism: The Potential of Asar Cave as a Natural Tourism Asset at Lenggong Valley, Perak - Rindam, Main (EDP Sciences, 2014)
The Lenggong Valley, from a standpoint of natural tourism research, presents strengths, weaknesses, opportunities and challenges that can be utilized to help increase the opportunities for the local community to increase their standard of living. Asar Cave comprises one of the caves that are found in Lenggong. A series of external studies have been done on Asar Cave in order to measure its potential for natural tourism in Lenggong. The objective of this study is to discuss caves as a natural resource that has great potential in the growth of the economy of the residents of the Lenggong Valley. Marketing caves as a source of nature tourism helps the government’s achievements in National Key Result Areas, apart from being a form of environmental control as well as helping to increase awareness about environmental education, specifically those associated with caves. The research results find that SWOT analysis presents huge potential for caves to become a source of nature tourism development in Lenggong. Great potential can also be seen from a standpoint of increasing the standard of living of its residents through their involvement in the tourism sector based on local natural assets.